2019
DOI: 10.1590/1678-992x-2017-0304
|View full text |Cite
|
Sign up to set email alerts
|

What explains the variation on the regenerative component dynamics of Araucaria Forests in southern Brazil?

Abstract: The natural regeneration process is essential for forest maintenance since it is critical for establishing new tree individuals. This study aimed to improve the understanding of the regenerative component dynamics of Araucaria Forests in Southern Brazil. We investigated the effects of climate, light, tree component structure and anthropogenic disturbance on tree species regeneration. Regenerating communities from six different fragments in forest remnants of the "Planalto Sul Catarinense" region was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
6
0
4
Order By: Relevance
“…However, despite the decrease in density in the plots, the species were more concentrated spatially in 2012 (FR: 3.2%) than in 2016 (FR: 4.1%). Other studies have also shown that this species had low representativeness (Dalla Rosa et al, 2016;Vefago et al, 2019). According to Dalla Rosa et al (2016), A. angustifolia has a limited number of regenerating individuals in the understory of the MOF and this limitation is even more extreme at high altitudes (>1,500 m).…”
Section: Phytosociological Parameters Of Natural Regenerationmentioning
confidence: 97%
See 2 more Smart Citations
“…However, despite the decrease in density in the plots, the species were more concentrated spatially in 2012 (FR: 3.2%) than in 2016 (FR: 4.1%). Other studies have also shown that this species had low representativeness (Dalla Rosa et al, 2016;Vefago et al, 2019). According to Dalla Rosa et al (2016), A. angustifolia has a limited number of regenerating individuals in the understory of the MOF and this limitation is even more extreme at high altitudes (>1,500 m).…”
Section: Phytosociological Parameters Of Natural Regenerationmentioning
confidence: 97%
“…Approximately half of the species (51.67%) were found in only 5% of the sample units, demonstrating the great diversity of species present in the regeneration of this forest type. In a study by Vefago et al (2019), Allophylus edulis and Matayba elaeagnoides were also among the most representative species. Araucaria angustifolia (Bertol.)…”
Section: Phytosociological Parameters Of Natural Regenerationmentioning
confidence: 97%
See 1 more Smart Citation
“…Para a regeneração natural, ainda foram obtidas as taxas de mudança para classes superiores (5) e inferiores de altura ( 6); e, para o componente arbóreo adulto, as taxas de perda em área basal (7) e ganho (8), assim como a mudança líquida (9) e a rotatividade (10) em área basal (ver GROSS et al, 2018;VEFAGO et al, 2019). ); mi = número de indivíduos que passaram para classes de tamanho inferiores; PAB = Taxa de perda em área basal (%.ano -1 ); AB 0 = Área basal no primeiro inventário (m 2 ); AB m = Área basal de árvores mortas (m 2 ); AB dec = decremento em área basal das árvores sobreviventes (m 2 ); GAB = Taxa de ganho em área basal (%.ano -1 ); AB r = Área basal das árvores recrutadas (m 2 ); AB cresc = crescimento em área basal das árvores sobreviventes (m 2 ); Rot AB = Taxa de rotatividade em área basal (%.ano -1 ) e ML AB = Taxa de mudança líquida em área basal (%.ano -1 ).…”
Section: Análise De Dadosunclassified
“…As taxas demográficas (e.g., mortalidade, recrutamento, ganho e perda em área basal) obtidas a partir dos estudos de dinâmica têm apresentado muitas variações de acordo com a floresta estudada (LIEBERMAN; LIEBERMAN, 1987), sendo que pouco se conhece sobre floresta nebular, o que torna maior a necessidade desses estudos, facilitando o planejamento de estratégias de conservação (HIGUCHI et al, 2008). Para a Floresta Ombrófila Mista, em escala regional, se a influência da altitude tem sido evidenciada como um importante fator na distribuição de espécies arbóreas (HIGUCHI et al, 2012), para os padrões de dinâmica e de regeneração natural, o efeito da fragmentação florestal (GROSS et al, 2018) e os distúrbios crônicos (VEFAGO et al, 2019) | Dinâmica do componente arbóreo e regenerante ... 1089 se mostram mais importantes. Além disso, observa-se que, enquanto o componente regenerativo frequentemente apresenta um padrão de estruturação (i.e., aumento na abundância de regenerantes) ao longo do tempo (VEFAGO et al, 2019), o componente adulto frequentemente demonstra um padrão de autodesbaste, com a redução do número de árvores acompanhado pelo aumento da área basal (GROSS et al, 2018).…”
Section: Introductionunclassified